Caregiver Perceptions of Mental Health and Barriers to and Facilitators of Their Child's Treatment. Issue 2 (February 2022) - Hellerova, Lenka; Gonzalez, Ariana E.; Dayan, Peter S.; George, Maureen
Abstract : Objectives: Nearly 1 million children visit emergency departments (EDs) annually for mental health crises. Caregivers play a critical role in the outcome of mental illness in their children, yet there is limited research on effective means to engage caregivers in the ED and provide the support they need. Our aim was to determine caregivers' perceptions about mental illness in their children, specifically regarding suicidality and depression, the impact of the children's mental health on the caregiver, and barriers to and facilitators of treatment. Methods: Guided by qualitative descriptive methodology, we conducted semistructured, open-ended interviews with a purposive sample of English-speaking primary caregivers of children 6 to 17 years old who presented with suicidal ideations or behaviors to 1 urban pediatric ED. Interviews were recorded and transcribed verbatim, and conventional content analysis was performed. Results: The participants (n = 20) were largely single ethnic-racial minority mothers. Content analysis identified 6 categories: caregivers' definitions of mental health, depression, and suicidality; perceived causes of mental illness; difficulty in identification of mental illness; the influence of the mental illness on caregivers; a complex network of communication among involved parties that resulted in the child's ED visit, as well as barriers to and facilitators of treatment. Conclusions: We identified several categories that encapsulate caregivers' perceptions of mental health and mental illness in their children and its effect on them. Future research should explore how inner-city EDs might partner with schools and trusted community-based organizations to enhance caregiver knowledge, reduce obstacles to care, increase screening for at-risk youth and implement strategies to optimize outcomes for children with depression and suicidal ideations. Abstract : Supplemental digital content is available in the text.